Fra glemte værker til iscenesættelse som form: Hotel Pro Formas opsætning af Rachmaninov Troika - Winkelhorn, Kathrine; Mølle Lindelof, Anja (Peripeti, 2021)
“Opera is an omnivorous monster. Opera is the result of countless skilled craftsmen, technicians, musicians, singers, artists and administrators work. Opera is passion. Opera is lie and truth in the purest form” as stage director Kirsten Dehlholm wrote in the program to Rachmaninov Troika – hers and Hotel Pro Forma’s staging of Sergei Rachmaninoff’s three operas: Aleko, The Miserly Knight and Fransisca da Rimini produced by the Belgian opera, La Monnaie in Brussels, June 2015 - the first time these three operas were being staged together. In this article we discuss the concept of the art work by examining how Rachmaninov Troika balances between 1) revitalizing these three more or less forgotten music historical operas and/or is creating a new piece of work.